2017
DOI: 10.1017/s0885715617000276
|View full text |Cite
|
Sign up to set email alerts
|

Combining XRD and XRF analysis in one Rietveld-like fitting

Abstract: X-ray diffraction (XRD) and X-ray fluorescence (XRF) are widely used analytical techniques for materials characterization; the information they provide can be considered complementary, as the former is mostly used to obtain crystallographic information and analyze phase content, whereas the latter is sensitive to elemental composition. Many researchers and technologists working in a variety of application fields already use them together in some sort of a “combined” approach, by separately performing XRD and X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…The phase analysis was performed by using ICDD (PDF-2, 2012) files. Both structural and microstructural parameters were determined from the refinements of XRD patterns using MAUD program (version 2.55) based on the Rietveld method [31].…”
Section: Characterizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The phase analysis was performed by using ICDD (PDF-2, 2012) files. Both structural and microstructural parameters were determined from the refinements of XRD patterns using MAUD program (version 2.55) based on the Rietveld method [31].…”
Section: Characterizationmentioning
confidence: 99%
“…Using the Rietveld refinement and Warren-Averbach method [24,25] in the frame of MAUD software [31], a detailed analysis of XRD profiles can be performed leading to the determination of phase composition in addition to structural and microstructural parameters for each phase, such as lattice parameters ( , , ), the average crystallite size ⟨ ⟩, microstrain ⟨ 2 ⟩ 1/2 , and stacking fault probabilities (SFP).…”
Section: Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has already been demonstrated that the combined application of XRD and XRF from both an experimental and analytical point of view is a powerful tool for material characterization. The extension of the combined approach also to RS for the phase identification and quantification in drill core samples is part of the objectives of the SOLSA project (G.A.…”
Section: Introductionmentioning
confidence: 99%